A concept analysis of immediate newborn care within 48 h of birth: A facility based - Eteaner Ntupanyama-Phiri; Charity Kabondo; Joseph Msambathukuta Chasweka; Felix Chisoni; Rodwell Gundo; Ellen Chirwa (Elsevier, 2024)
Background: Immediate newborn care interventions provided by midwives within 48 h of birth are invaluable in the reduction of neonatal morbidity and mortality. The purpose of this concept analysis is to clarify the meaning of immediate newborn care within 48 h of birth in relation to its attributes, antecedents, consequences and empirical referents. Methods: Walker and Avant's (2019) framework was used to analyze the concept. The framework consist of the following steps: selecting a concept; determining the aims of the analysis; identifying all the uses of the concept; identifying the defining attributes; identifying and constructing model, borderline, related and contrary cases; identifying antecedents and consequences; and finally defining empirical referents. Results: The attributes of immediate newborn care are up to date knowledge, proficiency in skills, effective communication, willingness, responsibility, compassionate, honesty, commitment, resilience, touch and patience. The identified antecedents are availability of adequate midwives, pre-service and in-service training, availability of functioning equipment and supplies, regular supervision, follow up and mentorship. The consequences include: improved provider's performance, client/caretaker's satisfaction, provider's growth and satisfaction, and reduction in neonatal morbidity and mortality. Conclusion: Immediate newborn care within 48 h helped in highlighting interventions that can be implemented immediately after child birth in order to reduce neonatal deaths.